DOI: 10.11606/d.22.2016.tde-16062015-191711
|View full text |Cite
|
Sign up to set email alerts
|

Carga de trabalho e absenteísmo da equipe de enfermagem em unidade de terapia intensiva

Abstract: Trata-se de um estudo transversal descritivo e retrospectivo com o objetivo de identificar a carga de trabalho e as taxas de absenteísmo da equipe de enfermagem de uma Unidade de Terapia Intensiva-Adulto (UTI) de um hospital de ensino no interior do estado de São Paulo. A população de estudo foi composta por duas partes: a primeira por todos os pacientes que permaneceram internados, no período de 01/01/2014 a 31/01/2014, totalizando 53 pacientes, e a segunda parte por relatórios gerenciais da unidade de saúde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…However, in this environment, time off and work overload problems and difficulty maintaining efficiency appear to be even more critical. 13 When the absences related to the work shift were analyzed, the results of the study presented here show that the morning shift presented the highest incidence in the ICU II group, and was statistically significant in relation to the afternoon and evening shifts, which had identical values for absences. This fact is in line with data from another study that used a sample of professionals working in the various department of two hospitals, which showed lower occurrences of sick leave in the night shift, and the highest rate occurred in the morning.…”
Section: /11mentioning
confidence: 58%
See 3 more Smart Citations
“…However, in this environment, time off and work overload problems and difficulty maintaining efficiency appear to be even more critical. 13 When the absences related to the work shift were analyzed, the results of the study presented here show that the morning shift presented the highest incidence in the ICU II group, and was statistically significant in relation to the afternoon and evening shifts, which had identical values for absences. This fact is in line with data from another study that used a sample of professionals working in the various department of two hospitals, which showed lower occurrences of sick leave in the night shift, and the highest rate occurred in the morning.…”
Section: /11mentioning
confidence: 58%
“…The average NAS was 66.9 points, with a minimum of 49.3 and a maximum of 94.6 points. 13 Researchers highlight that by applying the NAS in the adult ICU in Brazil, the average values of nursing workload were found to be between 61.97 and 81.2, i.e., values above what is considered overload (NAS≥51%). 14 A study conducted in the trauma ICU indicated an average nursing workload of 73.40 points (minimum of 35.00 and maximum of 123.00 points), a result that characterizes high work demand o, and is approximately the same or higher than in other Brazilian studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to standardize the language of the diagnoses was a handbook by NANDA, in which the actual diagnoses and risk are listed with their defining characteristics and related factors, establishing an agreement on the rules for the use of certain terms. 10 The main nursing diagnoses were:…”
Section: Research the Relationship Between The Nursing Diagnosis And Cognition Tests Performed On Elderlies With Alzheimer's Diseasementioning
confidence: 99%